PRAKTIK KERJA MENINGKATKAN AKSESIBILITAS KOLEKSI PERPUSTAKAAN POLITEKNIK PARAWISATA PALEMBANG - Shastillah, Shastillah (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
The crucial role of book labeling is in increasing the accessibility of library collections, which is a vital factor in maximizing the library's function as an information center. Good accessibility allows visitors, both students and researchers, to find and utilize available resources efficiently. Through a clear and consistent tagging system, users can quickly identify the category and location of the book they are looking for. This report examines various methods of labeling books, including the use of modern technology such as QR codes and digital library applications, which can speed up the accessibility process. This research covers the challenges faced in implementing an effective ngebeling system, such as limited budgets and the need for staff training. The aim of this research is to analyze how library materials are managed in the Tourism Polytechnic library. This research was conducted using qualitative methods based on the results of observations and experiences during Field at the Tourism Polytechnic library. The results obtained are ways of managing library materials Tourism Polytechnic library, namely stock taking, weeding, inputting, labeling, barcoding, and preparing library materials.